2020
DOI: 10.1175/jtech-d-19-0132.1
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Wind Observations from Open-Ocean Buoys: Correction for Flow Distortion

Abstract: The comparison of equivalent neutral winds obtained from (i) four WHOI buoys in the subtropics and (ii) scatterometer estimates at those locations reveals a root-mean-square (RMS) difference of 0.56–0.76 m s−1. To investigate this RMS difference, different buoy wind error sources were examined. These buoys are particularly well suited to examine two important sources of buoy wind errors because 1) redundant anemometers and a comparison with numerical flow simulations allow us to quantitatively assess flow dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Schlundt et al (2020) compared satellite and ASIMET wind measurements from other Ocean Reference Stations in the trade winds regions, including NTAS, and observed that wind speed discrepancies were less than 5% and consistent with flow distortion from CFD simulations (Emond et al, 2012). An empirical correction to the flow distortion exists that reduces the wind speed error to 5% of the true wind (Bigorre et al, 2013;Schlundt et al, 2020). This correction was not implemented here, as the flow distortion and platform motion errors are small at NTAS and do not impact our conclusions.…”
Section: In Situ Meteorology and Fluxesmentioning
confidence: 81%
See 2 more Smart Citations
“…Schlundt et al (2020) compared satellite and ASIMET wind measurements from other Ocean Reference Stations in the trade winds regions, including NTAS, and observed that wind speed discrepancies were less than 5% and consistent with flow distortion from CFD simulations (Emond et al, 2012). An empirical correction to the flow distortion exists that reduces the wind speed error to 5% of the true wind (Bigorre et al, 2013;Schlundt et al, 2020). This correction was not implemented here, as the flow distortion and platform motion errors are small at NTAS and do not impact our conclusions.…”
Section: In Situ Meteorology and Fluxesmentioning
confidence: 81%
“…Using data from a mooring deployed in the Gulf Stream, where high winds and currents induced significant platform motion and tilt, Bigorre et al (2013) showed that the total wind speed error could reach up to 10% of the true wind in these extreme conditions. Schlundt et al (2020) compared satellite and ASIMET wind measurements from other Ocean Reference Stations in the trade winds regions, including NTAS, and observed that wind speed discrepancies were less than 5% and consistent with flow distortion from CFD simulations (Emond et al, 2012). An empirical correction to the flow distortion exists that reduces the wind speed error to 5% of the true wind (Bigorre et al, 2013;Schlundt et al, 2020).…”
Section: In Situ Meteorology and Fluxesmentioning
confidence: 87%
See 1 more Smart Citation
“…Forth and post-construction, the effects of the ORS structure on oceanic and atmospheric conditions must be measured to evaluate the reliability, representativeness, and quality of the ORS data. This evaluation step can limit platform derived errors leading to measurement bias, something that is of particular concern when seeking to produce long-term regionally representative monitoring records (Schlundt et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Note that, as with platform related wind distortion (Schlundt et al, 2020), large structures can distort ocean currents in their vicinity, leading to a measurement bias. This effect may, in turn, affect ocean properties locally (e.g., temperature and salinity) such that careful seasonal comparisons between Ieodo ORS and the ambient area are required to identify whether these observations are representative, without substantive distortion.…”
Section: Temperature and Salinity In The Water Columnmentioning
confidence: 99%